100 views
2 votes
If y= 3x^2 + 2x/ 2x^2 - 3 calculate dy/dx help me plz

If y= 3x^2 + 2x/ 2x^2 - 3 calculate dy/dx help me plz-example-1

1 Answer

3 votes

Option A:


$(dy)/(dx)= (-2(2x^2+9x+3) )/((2x^2-3)^2)$

Solution:

Given
$y=(3x^2+2x)/(2x^2-3) $

To calculate
(dy)/(dx):


$(dy)/(dx)=(d)/(dx)((3x^2+2x)/(2x^2-3)) $

Using differential rule:


$(d)/(dx)((u)/(v) ) =(v(du)/(dx)-u(dv)/(dx) )/(v^2)$

Here,
u=3x^2+2x and
v=2x^2-3


$(d)/(dx)((3x^2+2x)/(2x^2-3)) =((2x^2-3)(d)/(dx)(3x^2+2x)-(3x^2+2x)(d)/(dx)(2x^2-3) )/((2x^2-3)^2)$ – – – – (1)

Now, using another differential rule:
(d)/(dx) x^n=nx^(n-1) and
(d)/(dx) (a)=0, a=constant


$(d)/(dx)(3x^2+2x) =6x+2 – – – – (2)


$(d)/(dx)(2x^2-3) =4x – – – – (3)

Substitute (2) and (3) in (1), we get


$(d)/(dx)((3x^2+2x)/(2x^2-3)) =((2x^2-3)(6x+2)-(3x^2+2x)(4x) )/((2x^2-3)^2)$

Now, simplifying the above equation


$=((12x^3+4x^2-18x-6)-(12x^3+8x^2) )/((2x^2-3)^2)$


$=(12x^3+4x^2-18x-6-12x^3-8x^2 )/((2x^2-3)^2)$


$=(-4x^2-18x-6 )/((2x^2-3)^2)$

Take –2 as common factor in numerator of the fraction.


$=(-2(2x^2+9x+3) )/((2x^2-3)^2)$


$(dy)/(dx)= (-2(2x^2+9x+3) )/((2x^2-3)^2)$